2005
DOI: 10.1128/aem.71.9.5244-5253.2005
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Prediction of Viruses in Shellfish

Abstract: A database was probed with artificial neural network (ANN) and multivariate logistic regression (MLR) models to investigate the efficacy of predicting PCR-identified human adenovirus (ADV), Norwalk-like virus (NLV), and enterovirus (EV) presence or absence in shellfish harvested from diverse countries in Europe (Spain, Sweden, Greece, and the United Kingdom). The relative importance of numerical and heuristic input variables to the ANN model for each country and for the combined data was analyzed with a newly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Our results are in line with other ecological studies in literature which compared the two methods and found ANN models more accurate than MLR (e.g. Lek et al, 1996;Paruelo and Tomasel, 1997;Brion et al, 2005). The strength of ANN lies in its fully inductive approach, which allows multidimensional relationships to be investigated without a priori knowledge of the shape of these relations.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are in line with other ecological studies in literature which compared the two methods and found ANN models more accurate than MLR (e.g. Lek et al, 1996;Paruelo and Tomasel, 1997;Brion et al, 2005). The strength of ANN lies in its fully inductive approach, which allows multidimensional relationships to be investigated without a priori knowledge of the shape of these relations.…”
Section: Discussionsupporting
confidence: 91%
“…Work is currently ongoing within CEN to produce a standard method based on this technology. Brion et al (2005) showed that, for three European countries, the occurrence of norovirus varied significantly between the countries and that additionally, presence was associated with area within the country, month, bacteriophage (somatic coliphage, F+-bacteriophage and B. fragilis phage) concentrations and species of mollusc being important. The relative importance of factors varied among the countries ± it may therefore be necessary to undertake regional, national or local risk profiles when determining the factors to be included in risk management strategies.…”
Section: Noroviruses In Bivalvesmentioning
confidence: 97%
“…Deoxyribonucleic acid (DNA) is considered as a promising material for molecular computing, which involves logical calculations , and solving complex mathematical problems based on the chemical reactions between molecules. Owing to Watson–Crick pairing, DNA information binding with paired sequences is widely used in traditional biotechnologies such as polymer chain reaction (PCR), gene editing and synthesis, , and molecule sensing, as well as for bionanotechnologies such as superlattices, DNA origami, and DNA computing. , The chemical reaction network (CRN), which is conducted through parallel and cascading reactions in the DNA solution enables solving problems via DNA biocomputing, which includes logic gate calculations, neural networks, , cell computing, and virus detection using neural networks. , However, several sequential CRN steps are required for implementing simple DNA-based logic gates; these steps are typically demonstrated in a single, small PCR tube or a plate reader by adding molecules using a pipet. , For example, Qian et al . designed CRNs for basic logic gates such as the AND, OR, and NOT gates by using four or five sequential steps .…”
Section: Introductionmentioning
confidence: 99%
“…14,15 The chemical reaction network (CRN), which is conducted through parallel and cascading reactions in the DNA solution enables solving problems via DNA biocomputing, which includes logic gate calculations, 16 neural networks, 17,18 cell computing, 19 and virus detection using neural networks. 20,21 these steps are typically demonstrated in a single, small PCR tube or a plate reader by adding molecules using a pipet. 22,23 For example, Qian et al designed CRNs for basic logic gates such as the AND, OR, and NOT gates by using four or five sequential steps.…”
Section: Introductionmentioning
confidence: 99%